Perspektif Pendidikan Agama Kristen Terhadap Pendidikan Progresivisme - Go Heeng; Antonius Sinaga; Yunardi Kristian Zega; Megariana Megariana; Efvi Noyita (Sekolah Tinggi Teologi Real Batam, 2023)
The correlation between progressivism education and Christian education lies in the same importance, namely producing students who have the ability and expertise from extracting students' talents and interests to the maximum in the learning process. Progressivism born with DNA necessitates a change in a more progressive direction. The values brought by progressivist education when faced with Christian religious education need to go through a selective process. This is because the basis for the development of this education system has differences. Progressivism education is built with the worldly concept of achieving world achievements, while Christian education is built with the concept of eternity because it is related to faith in Christ. The analysis found by the author regarding the perspective of Christian education on progressivism education, among others: 1) dynamic truths for progressivist education do not apply to Christian education because the truth in Christian education is final, 2) too giving freedom to students without providing clear boundaries, while for Christian education freedom is limited by the values of Christ. 3) the role of teachers is very important for students in Christian education because in addition to providing knowledge, teachers must also provide examples of living in accordance with Christ.Keywords: Christ; christian religious education; progressivism education AbstrakKorelasi antara pendidikan progresivisme dengan pendidikan agama Kristen terletak pada kepentingan yang sama yaitu melahirkan peserta didik yang memiliki kemampauan dan keahlian dari penggalian bakat dan minat peserta didik secara maksimal dalam proses pembelajaran. Progresivisme terlahir dengan DNA mengharuskan sebuah perubahan ke arah yang lebih maja kemajuan. Nilai-nilai yang dibawa oleh pendidikan progresivisme ketika diperhadapkan dengan pendidikan agama Kristen perlu melalui proses yang selektif. Hal ini karena dasar pembangunan sistem pendidikan ini memiliki perbedaan. Pendidikan progresivisme dibangun dengan konsep duniawi yaitu terletak kepada pencapain pencapain dunia, sementara pendidikan agama kristen dibangun dengan konsep kekekalan karena berkaitan dengan iman di dalam Kristus. Analisis yang ditemukan penulis perihal perspektif pendidikan agama kristen terhadap pendidikan progresivisme, antara lain: 1) kebenaran yang bersifat dinamis bagi pendidikan progresivisme tidak berlaku bagi pendidikan agama Kristen karena kebenaran pada pendidikan agama Kristen sudah final, 2) terlalu memberikan kebebasan pada peserta didik tanpa memberikan batasan-batasan yang jelas, sementara bagi pendidikan agama Kristen kebebasan dibatasi dengan nilai-nilai Kristus. 3) peran guru sangat penting bagi peserta didik dalam pendidikan agama Kristen karena selain memberikan ilmu guru juga harus memberikan teladan hidup yang sesuai dengan Kristus.Kata kunci: Kristus; pendidikan agama kristen; pendidikan progresivisme